Numerical study and pilot evaluation of experimental data measured on specimen loaded by bending and wedge splitting forces (Fracture and Structural Integrity, 2016)
The fracture mechanical properties of silicate based materials are determined from various fracture mechanicals tests, e.g. three- or four- point bending test, wedge splitting test, modified compact tension test etc. For evaluation of the parameters, knowledge about the calibration and compliance functions is required. Therefore, in this paper, the compliance and calibration curves for a novel test geometry based on combination of the wedge splitting test and three-point bending test are introduced. These selected variants exhibit significantly various stress state conditions at the crack tip, or, more generally, in the whole specimen ligament. The calibration and compliance curves are compared and used for evaluation of the data from pilot experimental measurement.
Keywords: Numerical simulation; Stress intensity factor; T-stress; Concrete; Finite element method; Wedge splitting test; Three–point bending test